Tipikal Kualitas Mata Air Sebagai Sumber Air Minum Masyarakat - Hindun Adelia Safitri; Esti Sarjanti (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2023)
There are 3 springs used by the people in Kuta Village, namely Setu River, Sirah River, and Depok River. This study aims to examine typical water quality based on physical, chemical, and microbiological parameters in Kuta Village, Belik District, Pemalang Regency. The method used in this research is the survey method. Observed water quality data includes physical properties, chemical properties, and biological properties. The sampling technique uses total sampling. Data collection was carried out by observing ex-situ for parameters tested in the laboratory and in situ for parameters that could be observed in the field. Data analysis by matching laboratory test results with PERMENKES RI No. 32 of 2017 concerning drinking water quality requirements. The results showed the physical properties parameters: temperature, odor, color, total dissolved solids, turbidity, and taste. Chemical properties: pH, Nitrate, Nitrite, Ammonia, and Manganese acidity levels are proven to be feasible. As for the biological characteristics: the presence of E-colli bacteria and Coliform bacteria throughout the Kuta Village Springs is no longer feasible. In general, water from the Kali Setu, Kali Sirah, and Kali Depok springs is included in class B water.